Amplification of Stick-Slip Events Through Lubricated Contacts in Consolidated Granular Media - Melo-Hurtado, F; Galaz-Donoso, B (American Physical Society, 2018)
The influence of lubricated contacts on the stick-slip behavior of a granular system is investigated. Samples of cylindrical shape made of glass spheres confined at a constant pressure and subjected to gradual deformation along their main axis are considered. Under constant axial deformation, the granular compact exhibits a regular stick-slip regime, in which gradual stress loading (stick) is followed by rapid relaxation events or failure (slip). The amplitude of stress drops (slips) and their recurrence time are investigated as a function of the amount of lubricant fluid. In the absence of lubricant, stress drops are very frequent but their amplitude is relatively small. However, the addition of a minute volume of lubricant into the granular packing, increases both the amplitude of stress drops and their recurrence time, following a saturating exponential loading curve with the lubricant volume. We show that the typical volume at which saturation occurs corresponds to the amount of fluid required to completely cover the surface of the spheres, with the thickness of the coat corresponding to the size of the asperities. These results support the idea that, to a certain extent, adding lubricant reduces sliding friction, as well as synchronously mobilizes a set of contacts. © 2018 American Physical Society.